Analisis Kemampuan Literasi Numerasi Pada Siswa Madrasah Ibtidaiyah - Tamarin, Vina; Mangkuwibawa, Hilman; Marthyane Pratiwi, Inne (Bidayatuna, 2024)
The purpose of this study is to assess the numeracy literacy skills of Madrasah Ibtidaiyah fifth grade pupils and ascertain the challenges these kids face in this area. The study's descriptive methodology, which employed a qualitative approach, was applied to fifth-grade pupils at MI Al-Misbah Bandung City. Tests, interviews, and documentation served as the research's instruments. Techniques for data analysis, reduction, presentation, and conclusion are used in this study. According to the study's findings, class V pupils at MI Al-Misbah Al-Misbah in Bandung City scored an average of 54 on the numeracy literacy test. Ten of the 58 students who started the course finished it. The challenges that pupils face, both internal and external (internal and external), are described as supporting the deficiency in numeracy literacy skills. There are numerous additional reasons that contribute to a lack of numeracy literacy skills among students, therefore it is determined that class V MI students' numeracy literacy abilities are not the only reason why troublesome pupils struggle. Al-Misbah Al-Misbah from the purchase of Bandung City When considering the challenges that pupils face, the average score goes into the low range.